Achieving climate-smart coffee in Central America - Bunn, Christian (International Center for Tropical Agriculture, 2019)
This document is a climate –smart coffee profile for Central America. It summarizes the results of a climate analysis made for the region. This brief is divided in 4 sections to guide adaptation at scale: Towards resilient production at scale, Recommendation domains to scale climate smart coffee, Scaling climate smart coffee, Climate smart coffee practices.